Risk factors for recurrent cerebral amyloid angiopathy-related intracerebral hemorrhage - Jia, Xinglei; Bo, Menghan; Zhao, Hong; Xu, Jia; Pan, Luqian; Lu, Zhengyu (Frontiers in Neurology, 2023)
Background Cerebral amyloid angiopathy (CAA) is the most common cause of lobar intracerebral hemorrhage (ICH) in the elderly, and its multifocal and recurrent nature leads to high rates of disability and mortality. Therefore, this study aimed to summarize the evidence regarding the recurrence rate and risk factors for CAA-related ICH (CAA-ICH). Methods We performed a systematic literature search of all English studies published in PubMed, Embase, Web of Science, Cochrane Library, Scopus, and CINAHL from inception to June 10, 2023. Studies reporting CAA-ICH recurrence rates and risk factors for CAA-ICH recurrence were included. We calculated pooled odds ratios (ORs) with their corresponding 95% confidence intervals (CIs) using a random/fixed-effects model based on the I2 assessment of heterogeneity between studies. Publication bias was assessed using Egger's test. Results Thirty studies were included in the final analysis. Meta-analysis showed that the recurrence rate of CAA-ICH was 23% (95% CI: 18–28%, I2 = 96.7%). The risk factors significantly associated with CAA-ICH recurrence were: previous ICH (OR = 2.03; 95% CI: 1.50–2.75; I2 = 36.8%; N = 8), baseline ICH volume (OR = 1.01; 95% CI: 1–1.02; I2 = 0%; N = 4), subarachnoid hemorrhage (cSAH) (OR = 3.05; 95% CI: 1.86–4.99; I2 = 0%; N = 3), the presence of cortical superficial siderosis (cSS) (OR = 2.04; 95% CI: 1.46–2.83; I2 = 0%; N = 5), disseminated cSS (OR = 3.21; 95% CI: 2.25–4.58; I2 = 16.0%; N = 6), and centrum semiovale-perivascular spaces (CSO-PVS) severity (OR = 1.67; 95% CI: 1.14–2.45; I2 = 0%; N = 4). Conclusion CAA-ICH has a high recurrence rate. cSAH, cSS (especially if disseminated), and CSO-PVS were significant markers for recurrent CAA-ICH. The onset of ICH in patients with CAA is usually repeated several times, and recurrence is partly related to the index ICH volume. Identifying clinical and neuroimaging predictors of CAA-ICH recurrence is of great significance for evaluating outcomes and improving the prognosis of patients with CAA-ICH. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=400240, identifier [CRD42023400240].